An Attempt Towards an Assessment of the Cerknica Polje Water Balance - Kovačič, Gregor (Acta Carsologica, 2010)
This paper deals with the water balance of the Cerknica Polje. The results of previous investigations are compared with the calculations of inflows to and outflows from the polje made for the hydrological year 1975 (411 days). The calculation of the Cerknica Polje water balance is made on the basis of daily volume variations of Lake Cerknica, calculated using the water level data of the Stržen stream at the Dolenje Jezero gauging station and the digital elevation model of the Cerknica Polje (grid cell size 25 x 25 m). For the hydrological year 1975, total runoff from the Cerknica Polje catchment (475 km2) is estimated at 620 million m3 of water or 17 m3/s. In the observation year, the strongest lake volume increase in terms of discharge was 135 m3/s, whereas the strongest lake volume decrease was 60 m3/s. According to calculations, maximum possible inflow to the Cerknica Polje was 232 m3/s. In the hydrological year 1975, calculated mean outflow from the Cerknica Polje through ponor caves and ponors at the bottom of the polje was 23.69 m3/s and maximum calculated outflow was 91.75 m3/s.